2017
DOI: 10.1016/j.canep.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignant childhood germ cell tumors in relation to demographic, gestational, and perinatal characteristics

Abstract: Background Childhood germ cell tumors (GCTs) are a rare assortment of neoplasms, with mostly unknown etiology, that are believed to originate very early in life. Few studies have examined risk factors by histologic subtype, despite evidence of different risk profiles. Materials and Methods In this population-based case-control study, 451 childhood malignant GCT cases ages 0–5 years were identified from the California Cancer Registry. Differentiating between common histologic subtypes, we identified 181 yolk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 41 publications
(44 reference statements)
5
32
1
Order By: Relevance
“…Childhood cancer was more common among children born to mothers with advanced age at pregnancy, White non‐Hispanic mothers, mothers with 16 or more years of education, mothers with less frequent prenatal care visits, and mothers whose prenatal care was paid by private insurance (Tables and ). Associations between demographic factors and specific cancer subtypes have been described previously . Mothers of children with any type of childhood cancer and controls were similar in terms of parity and birth type (singleton vs. multiple gestation), but distributions varied by cancer subtype.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Childhood cancer was more common among children born to mothers with advanced age at pregnancy, White non‐Hispanic mothers, mothers with 16 or more years of education, mothers with less frequent prenatal care visits, and mothers whose prenatal care was paid by private insurance (Tables and ). Associations between demographic factors and specific cancer subtypes have been described previously . Mothers of children with any type of childhood cancer and controls were similar in terms of parity and birth type (singleton vs. multiple gestation), but distributions varied by cancer subtype.…”
Section: Resultssupporting
confidence: 57%
“…Associations between demographic factors and specific cancer subtypes have been described previously. [5][6][7]20,21 Mothers of children with any type of childhood cancer and controls were similar in terms of parity and birth type (singleton vs. multiple gestation), but distributions varied by cancer subtype. Table 2 shows that case children had pregnancy characteristics and delivery outcomes distinct from control children.…”
Section: Resultsmentioning
confidence: 99%
“…As this was a record-based study, we did not seek informed consent from individual subjects. The demographic and gestational characteristics of cases and controls have been previously reported (Abrahao et al, 2015; Hall et al, 2016; Heck et al, 2012; Heck et al, 2013b; Heck et al, 2014, 2015; Heck et al, 2013c; Shrestha et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Multiple linkage studies have reported a prevalence of 2–3% of children with congenital anomalies in the general population (Hoyert et al, ; Yoon et al, ). Several large‐scale epidemiologic studies have provided substantial evidence of an association between congenital anomalies and cancer risk in children (Agha et al, ; Altmann, Halliday, & Giles, ; Bjorge, Cnattingius, Lie, Tretli, & Engeland, ; Botto et al, ; Carozza, Langlois, Miller, & Canfield, ; Hall, Ritz, Cockburn, Davidson, & Heck, ; Janitz et al, ; Mili, Khoury et al, ); Narod, Hawkins, Robertson, & Stiller, ; Rankin, Silf, Pearce, Parker, & Ward Platt, ; Rios et al, ; Windham, Bjerkedal, & Langmark, ). Studies have demonstrated significant associations specifically between neurological congenital anomalies and pediatric cancer (Altmann et al, ; Bjorge et al, ; Botto et al, ; Carozza et al, ; Narod et al, ), with some suggesting a specific link between neurological malformations and central nervous system tumors (Agha et al, ; Altmann et al, ; Bjorge et al, ; Narod et al, ).…”
Section: Introductionmentioning
confidence: 99%